Recurrence rates in primary spontaneous pneumothorax: a systematic review and meta-analysis. Issue 3 (6th September 2018) - Walker, Steven P.; Bibby, Anna C.; Halford, Paul; Stadon, Louise; White, Paul; Maskell, Nick A.
Primary spontaneous pneumothorax (PSP) recurrence rates vary widely in the published literature, with limited data describing the factors that influence recurrence. The aims of this systematic review were to determine an estimation of PSP recurrence rates and describe risk factors for recurrence. A systematic review was conducted of all studies reporting PSP recurrence. Electronic searches were performed to identify English language publications of randomised trials and observational studies. The population was adults with PSP, who underwent conservative management, pleural aspiration or chest drainage. The outcome of interest was recurrence. Articles were screened and data extracted from eligible studies by two reviewers. Of 3607 identified studies, 29 were eligible for inclusion, comprising 13 548 patients. Pooled 1-year and overall recurrence rates were 29.0% (95% CI 20.9–37.0%) and 32.1% (95% CI 27.0–37.2%), respectively. Female sex was associated with increased recurrence (OR 3.03, 95% CI 1.24–7.41), while smoking cessation was associated with a four-fold decrease in risk (OR 0.26, 95% CI 0.10–0.63). I 2 for random effects meta-analysis was 94% (p<0.0001), reflecting high heterogeneity between studies. This systematic review demonstrates a 32% PSP recurrence rate, with greatest risk in the first year. Female sex was associated with higher risk, suggesting possible sex-specific pathophysiology. PSP has a 32% recurrence rate, with almost all the risk in the first year. Smoking cessation decreases this risk four-fold. Females may be at higher risk, possibly due to sex-specific pathogenic mechanisms. http://ow.ly/Mty730kPi9z